Diálogo institucional entre o Supremo Tribunal Federal e o Congresso Nacional: um estudo sobre o compartilhamento da interpretação constitucional em sede de ação direta de inconstitucionalidade - VIANA, Pedro Nilson Moreira (2022)
This research aims to evaluate the relations stablished between Supremo Tribunal Federal and Congress with regard to the interpretation of the Constitution, based on the Institutional Dialogue theory. It reflects on the risks to democracy arising from judicial activism, as well as evaluate, currently, the position of the Brazilian Constitutional Court regarding the acts of the federal Legislator in order to identify, to what extent, the latter is able to maintain its interpretative authority on issues that are subject to constitutional review through ação direta de inconstitucionalidade from 1/1/2018 to 1/1/2022. Adopting an inductive methodology, with a qualitative and socio-juridical-critical bias, it is possible to observe that judicial protagonism does not result only from factors endogenous to the Judiciary Power, but is also related to the low legislative performance. In Brazil, there is a worrying sign of increased judicial control of legislative acts at the federal level, while it is observed that judicial revisionism by the Supremo Tribunal Federal is currently not as strong as it seems to be.